Implikasi Ebook Dalam Meningkatkan Literasi Keagamaan Siswa - Hanan, Muhammad Yahya; Asmuni, Hadiqoh; Habibah, Nur Faiz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2024)
The development of information technology has been widely felt in the human environment, especially in the realm of education and teaching in schools. The COVID-19 pandemic, which has necessitated online learning, has made technology more sought after in its application. In this condition, the use of e-books has become one form of utilizing information technology in the learning environment, including at MTsN 3 Banyuwangi. This study uses a quantitative approach with a correlational method with all students of MTsN 3 Banyuwangi as respondents. Based on the research results, it can be concluded that the use of e-books in schools can improve students' religious literacy, especially in reading and writing interests. The implementation of e-books at MTsN 3 Banyuwangi is quite good, as evidenced by several students who have increased their reading and writing interests in line with the level of students' activity in using e-books. However, there are obstacles faced by students in using e-books, such as students easily getting tired when reading using electronic media and difficulty accessing e-book materials, which are usually hindered by a signal. These obstacles can be minimized by the school by scheduling lessons and providing Wi-Fi facilities for students. Learning using e-books is indeed an effective step in learning, but still without reducing supervision of the students' learning process